STUDY OF PREOPERATIVE CLINICAL AND INVESTIGATIVE FACTORS PREDICTING DIFFICULT LAPAROSCOPIC CHOLECYSTECTOMY - Verma, Deepak; Ratan; Chand, Nemi (International Journal of Research -GRANTHAALAYAH, 2020)
Background: Laparoscopic cholecystectomy is one of the most commonly performed surgical procedure with the advantage of short hospital stay, cosmetic, less post-operative pain and early return to work and thus ultimately cost effective. However, certain factors can make the procedure difficult and such patients many do not enjoy benefit of laparoscopic procedure particularly longer hospital stay. Aim: To determine various factors on clinical, pathological and radiological grounds to predict difficult laparoscopic cholecystectomy. Material and Method: 200 patients admitted in surgical ward with a diagnosis of Chronic Calculus cholecystitis to be selected for laparoscopic cholecystectomy were subject of this study. Age, Sex, BMI, number of previous attack, previous abdominal surgery, past history of pancreatitis and jaundice, signs of acute cholecystitis, leucocytosis, CRP, Liver function tests, serum amylase and lipase, GB wall thickness, presence of pericholecystic fluid , status of GB and anatomical variation were various factors studied. Results: Age > 50 years, male sex, BMI>30, more than 4 attacks, signs of cholecystitis, leucocytosis > 11,000/cu mm, increased GB wall thickness, presence of pericholecystic fluid and overdistended or contracted gall bladder are associated with difficult laparoscopic cholecystectomy.